Plasmon aided (BiVO4)x–(TiO2)1−x ternary nanocomposites for efficient solar water splitting. (October 2017) - Ali, Shahid; Khan, Ibrahim; Khan, Safyan A.; Sohail, Manzar; Yamani, Zain H.; Morsy, Mohamed A.; Qamaruddin, Muhammad
Graphical abstract: Highlights: (BiVO4 )x –(TiO2 )1−x composites prepared via two-steps solvothermal method. Series shows improved PEC water splitting as compared to pristine BiVO4 and TiO2 . Ag NPs were incorporated to study the effect of surface plasmon resonance. Ag NPs further enhanced PEC performance of ternary composite via SPR effect. Ag/(BiVO4 )0.10 –(TiO2 )0.90 affirm prolonged photocurrent ( I   –   t ) stability until 1 h. Abstract: The work presents the results of newly synthesized facile plasmon aided nanocomposite series, ((BiVO4 )x –(TiO2 )1−x, x = 0.01, 0.05, 0.10 and 0.20) for the efficient solar-driven water splitting application. Owing prominent optoelectrical properties of B10 = (BiVO4 )0.10 –(TiO2 )0.90 composite, Ag nanoparticles (NPs) were impregnated to study the effect of surface plasmon resonance (SPR) phenomenon. A significant shift of 0.16° and 0.4 eV is recorded in X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) profiles, respectively which confirmed the formation of Ag/B10 nanocomposite. The micrograph and elemental mapping of Ag/B10 composite confirm a homogenous distribution of its components. A notable decrease in the band gap from 3.26 eV (TiO2 ) to 2.44 eV (Ag/B10) is estimated by Kubelka − Munk equation. Furthermore, the substantial decrease in photoluminescence (PL) intensity of Ag/B10 (∼7 folds of TiO2 ) corroborates its higher light absorption capacity and lower photo-excitons recombination. The photoelectrochemical (PEC) water splitting studies carried out via linear sweep voltammetry (LSV) demonstrate that all the photoanodes were active at ∼0.6 V. Whereas, chronoamperometry ( I   –   t ) results depicted the photocurrent density reached to the maximum value of ∼230 µA cm −2 at 0.6 V for Ag/B10 under chopped solar irradiations. Moreover, B10 and Ag/B10 nanostructures affirm prolonged photocurrent ( I   –   t ) stability until 3600 s. We report here for the first time, Ag/B10 ternary composite shows enhanced photocurrent density due to its narrow band gap, lower photo-excitons recombination and SPR effect as compared to pristine TiO2, BiVO4 and their binary composites.